BEING HOMOSEXUAL IN AN INCLUSIVE SCHOOL: THE INVESTIGATION OF THE DIFFICULTIES EXPERIENCED BY HOMOSEXUALS IN THEIR EDUCATIONAL LIFE TRAJECTORY - Silva, Renan Antonio [UNESP] (Fundacao Univ Tocantins, 2018)
This work focuses on the investigation of the difficulties experienced by homosexuals in their life course. It also investigates the reality lived by the students of the E-JOVEM school, a school in Campinas-SP focused on the LGBTTT public, verifying the possible transformations experienced both in the personal scope (learning, freedom, among others) and in the collective sphere, related to combat To homophobia). In this institution data collection took place in two stages: initially, observations were made in the school environment, followed by individual, semi-structured interviews with five students and five teachers. E-JOVEM seeks to heal with homophobia by providing socio-affective support among participating homosexuals in an innovative pedagogical project that enables social transformation and protection of individuals who are beaten in the face of prejudice. These forms of protection contribute to the process of building public policies aimed at the homossociability of LGBTTTs in contemporary society.
Keywords: LGBTTT; Homophobia; Education; Public policy; Human and Social Development